Ventricular-subventricular zone stem cell niche adaptations in a mouse model of post-infectious hydrocephalus - Herman, Julianna; Rittenhouse, Nicole; Mandino, Francesca; Majid, Mushirah; Wang, Yuxiang; Mezger, Amelia; Kump, Aidan; Kadian, Sumeet; Lake, Evelyn M. R.; Verardi, Paulo H.; Conover, Joanne C. (Frontiers in Neuroscience, 2024)
Congenital post-infectious hydrocephalus (PIH) is a condition characterized by enlargement of the ventricular system, consequently imposing a burden on the associated stem cell niche, the ventricular-subventricular zone (V-SVZ). To investigate how the V-SVZ adapts in PIH, we developed a mouse model of influenza virus-induced PIH based on direct intracerebroventricular injection of mouse-adapted influenza virus at two distinct time points: embryonic day 16 (E16), when stem cells line the ventricle, and postnatal day 4 (P4), when an ependymal monolayer covers the ventricle surface and stem cells retain only a thin ventricle-contacting process. Global hydrocephalus with associated regions of astrogliosis along the lateral ventricle was found in 82% of the mice infected at P4. Increased ependymogenesis was observed at gliotic borders and throughout areas exhibiting intact ependyma based on tracking of newly divided cells. Additionally, in areas of intact ependyma, stem cell numbers were reduced; however, we found no significant reduction in new neurons reaching the olfactory bulb following onset of ventriculomegaly. At P4, injection of only the non-infectious viral component neuraminidase resulted in limited, region-specific ventriculomegaly due to absence of cell-to-cell transmission. In contrast, at E16 intracerebroventricular injection of influenza virus resulted in death at birth due to hypoxia and multiorgan hemorrhage, suggesting an age-dependent advantage in neonates, while the viral component neuraminidase resulted in minimal, or no, ventriculomegaly. In summary, we tracked acute adaptations of the V-SVZ stem cell niche following onset of ventriculomegaly and describe developmental changes that help mitigate the severity of congenital PIH.